Amyloid Deposition: An Unusual Case of Deep Gluteal Syndrome and Sciatic Nerve Compression: A Case Report. Issue 3 (13th July 2022) - Parikh, Harin B.; Matcuk, George R.; Leong, Matthew; Vrahas, Mark S.; Seruya, Mitchel
Abstract : Case: Soft-tissue amyloidomas are exceedingly rare, with only a few cases reported in the literature. There are no reports of sciatic nerve compression secondary to a soft-tissue amyloidoma. We report a unique case of a 71-year-old man with an incidentally found amyloidoma who was initially believed to have deep gluteal syndrome. He had a favorable outcome after surgical decompression. Conclusion: For patients who do not have classic examination and electromyography/nerve conduction findings of piriformis syndrome, providers should explore other etiologies of peripheral nerve compression including soft-tissue amyloidoma.